PENGARUH JUMLAH DANA PIHAK KETIGA (DPK) NON PERFOMING FINANCING (NPF) DAN SERTIFIKAT BANK INDONESIA SYARI’AH (SBIS) TERHADAP PENYALURAN PEMBIAYAAN PERBANKAN SYARI’AH DI INDONESIA - Anshori, Arif Rijal (STIBANKS Al Ma'soem Bandung, 2019)
Banking is a very important part in the economy, one of them as intermediary institutions whose duty to collect funds from the public and then channel them back in the form of financing.This study aims to determine the effect Number of DPK, NPF and SBIS partially to finance portfolio of Islamic banking in Indonesia, and to determine the effect Number of DPK, NPF and SBIS simultaneously to the finance portfolio of Islamic banking in Indonesia.This study proceed from the assumption that (1) the size distribution of the funds offered by Islamic banks is very influenced by the size DPK means that the higher the number of third-party funds collected, the higher also finance portfolio, (2) the higher non-performing financing the worse the quality of banking assets, (3) the higher the bonus level set SBIS Indonesian bank will lower the financing undertaken by the banking Shari'ah. But based on data from Islamic banking statistics from the years 2008-2014 there is a gap between theory and facts on the ground. These assumptions are tested empirically so that the truth can be scientifically recognized. When there is a justification or rejection of these assumptions, then this is a scientific truth that can be considered Islamic banking in Indonesia.Quantitative research methods in this study using research formats explanation, source data used in this research is secondary data, then the type of data used in this research is quantitative data time series, the quarterly data of financing, deposits, NPF and SBIS Islamic banking in Indonesia from 2008 to 2014. Data were then processed by means of statistical analysis using Eviews 7, which comprises the classical assumption of them: normality test, heteroscedasticity, multicollinearity test, autocorrelation test. statistical tests include: regression, t test, F test and R2.The conclusion that can be drawn from this study that partially, DPK variable is positive and significant effect on the financing, NPF variable is negative but not significant effect on the financing, while SBIS is negative and significant effect on the financing. Then simultaneously the number of DPK, NPF and SBIS significant effect on the distribution of funding. Those variables could explain freely by 99.45% and the remaining 0.55% can be explained by other variables not examined.